Effectiveness of sub gingival irrigation of an indigenous 1% curcumin solution on clinical and microbiological parameters in chronic periodontitis patients: A pilot randomized clinical trial - Gottumukkala, Sruthima N. V. S. (Medknow Publications & Media Pvt Ltd, 2013)
AIM: The aim of this study is to evaluate the efficacy of 1% curcumin (CU) solution and compare it with conventional irrigant i.e., 0.2% chlorhexidine (CHX) gluconate and a positive control (saline) as an adjunct to thorough scaling and root planing. MATERIALS AND METHODS: A total of 23 patients with non-adjacent probing pocket depths (PPDs) ≥5mm were randomly assigned to CHX, CU and positive control irrigation groups and subjected to randomized single blinded clinical control trial. The clinical parameters bleeding on probing, redness, plaque index, PPD and microbiological parameter N-benzoyl-DL-arginine-2-naphthylamide (BANA) test were evaluated at baseline, 1, 3 and 6 months interval. RESULTS: At 1 month evaluation, CU group showed better results compared with the other groups. However, by the end of the study period CHX group showed the best results with as light recurrence in the CU group. The results of BANA test showed similar results for both CU and CHX group throughout the study period. CONCLUSION: The results of this study show a mild to moderate beneficiary effect of CU irrigation when used as an adjunct to Scaling and root planing. Further studies may be required using varied concentrations of the drug to improve the substantivity of the drug and also to prevent early re-colonization of periodontal pathogens.